ANALISIS PENGETAHUAN LINGKUNGAN DAN PERILAKU RAMAH LINGKUNGAN BERDASARKAN GENDER DAN TINGKAT PENDIDIKAN DI KOTA PEKANBARU - Julina - (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
This study attempted to investigate whether there are differences in knowledge about the environment and eco-friendly purchasing behavior based on gender and education. Data were collected using questionnaire containing questions about environmental knowledge and eco-friendly behavior based on previous research. Collected data were analyzed using descriptive and quantitative techniques. Multivariate Analysis of Variance (MANOVA) was used to determine the influence of gender and education level of knowledge and eco-friendly behavior. Results of univariate model testing found that in terms of gender, the gender differences found significant influence on both purchase decisions of environmentally friendly and environmental knowledge. While the the education level influence on of environmental knowledge, but it does not affect the environmentally friendly purchasing decisions. Based on these findings, it is expected that integrate relevant aspects of environmental conservation in all levels of education, and so is strengthening the role of each gender to support the creation of an enabling environment both for current and future generations.